Chemical and morphological features of nanofilled composite resin: influence of finishing and polishing procedures and fluoride solutions - Oliveira, Ana Luísa Botta Martins de [UNESP]; Santos, Patrícia Aleixo dos; Palma-Dibb, Regina Guenka; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Wiley, 2012)
This study evaluated the inﬂuence of ﬁnishing and polishing procedures and differ-ent ﬂuoride solutions on superﬁcial morphology and chemistry of the nanoﬁlled composite resinSupreme XT (3M) through the EDX analysis and SEM evaluation. Circular specimens (n 5 30) of 10mm diameter and 2 mm thickness were prepared, with half of the sample assays ﬁnished and polishedwith Super-Snap1sandpaper. The experimental groups were divided according to the presence or ab-sence of ﬁnishing and polishing and solutions (arti ﬁcial saliva, 0.0 5% of manipulated sodium ﬂuoridesolution, Fluordent Re ach, Oral B, Fluorgard). Specimens were immersed in each respective solutionfor 1 min per day, during 60 days and stored in artiﬁcial saliva at 37 6 18C between immersion peri-ods. Topography and chemical analysis was qualitative. It was observed that specimens submitted toﬁnishing and polishing procedures had lower superﬁcial degradation. Fluoride solutio ns promoted su-perﬁcial alterations on specimens, being the highest degradation obtained with Fluordent Reach. Itca n be concluded that ﬁnishing and polishing procedures and the immersion media inﬂuence the su-perﬁcial morphology of composite resin tested; the Fluordent Reach was the ﬂu oride solution thatmo st affected the material’s surface.
Keywords: Dental polishing; Fuorine; Composite resins; EDX; SEM; Resina composta; Acabamento; Soluções flouretadas; Alteração de cor